2010
DOI: 10.1021/ja106343h
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-tert-Butyl-2,6-dimethylphenylsulfur Trifluoride as a Deoxofluorinating Agent with High Thermal Stability as Well as Unusual Resistance to Aqueous Hydrolysis, and Its Diverse Fluorination Capabilities Including Deoxofluoro-Arylsulfinylation with High Stereoselectivity

Abstract: Versatile, safe, shelf-stable, and easy-to-handle fluorinating agents are strongly desired in both academic and industrial arenas, since fluorinated compounds have attracted considerable interest in many areas, such as drug discovery, due to the unique effects of fluorine atoms when incorporated into molecules. This article describes the synthesis, properties, and reactivity of many substituted and thermally stable phenylsulfur trifluorides, in particular, 4-tert-butyl-2,6-dimethylphenylsulfur trifluoride (Flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 289 publications
(188 citation statements)
references
References 43 publications
3
182
0
3
Order By: Relevance
“…This is consistent with Umemoto's finding that PhSF 3 is considerably less effective than Fluolead in its reactions in DCE [14]. The interesting thing about the current results, however, is that PhSF 3 , under our in situ reaction conditions in acetonitrile, appears to be essentially untouched by the added benzaldehyde reactant.…”
Section: Alternative Arylsulfur Trifluoridessupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with Umemoto's finding that PhSF 3 is considerably less effective than Fluolead in its reactions in DCE [14]. The interesting thing about the current results, however, is that PhSF 3 , under our in situ reaction conditions in acetonitrile, appears to be essentially untouched by the added benzaldehyde reactant.…”
Section: Alternative Arylsulfur Trifluoridessupporting
confidence: 91%
“…Benzaldehyde (0.75 equiv.) was then added and the mixture allowed to stir at room temperature with no significant amount of product being observed after 24 h. Umemoto had shown that the reaction of Fluolead with aldehydes is complete at room temperature after 20 h when the reaction is carried out in 1,2-dichloroethane (DCE) (Scheme 1) [14]. Thus the mixture of in situ-generated Fluolead in acetonitrile is less reactive than that of pure Fluolead in DCE.…”
Section: In Situ Use Of Fluoleadmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfur tetrafluoride and the following compounds can be used for the controlled introduction of fluorine into organic compounds: Dialkylaminosulfur(IV) fluorides (R 2 NSF 3 ) [44][45][46], arylsulfurtrifluorides [47], fluoroalkylamines (e.g., 2-chloro-1,1,2-trifluoroethyldiethylamine or 1,1,2,3,3,3-hexafluoropropyldiethylamine), tetra-n-butylammonium fluoride, amine hydrofluorides, nitrosyl fluoride, perchloryl fluoride, fluoroxyfluoroalkanes (e.g., CF 3 OF) [48], xenon difluoride [49], CH 3 COOF [50], N-fluoropyridinium salts [51], N-fluorosulfonimides [52], and Selectfluor [53]. They are of commercial value for the fluorination of complex organic compounds, such as pharmaceuticals.…”
Section: Fluorination With Nonmetal Fluoridesmentioning
confidence: 99%
“…2 When the replacement is carried out with DAST 8a or Deoxo-Fluor™, 8b 11:89 and 28:72 mixtures of α-and β-isomers are obtained.…”
Section: Introductionmentioning
confidence: 99%